Investigating plasma modifications and gas-surface reactions of TiO2-based materials for photoconversion - Pulsipher, Daniel J. V., author; Fisher, Ellen R., advisor; Elliott, C. Michael, committee member; Van Orden, Alan, committee member; Strauss, Steven H., committee member; Yalin, Azer, committee member (Colorado State University. Libraries, 2012)
Plasmas offer added flexibility for chemists in creating materials with ideal properties. Normally unreactive precursors can be used to etch, deposit and modify surfaces. Plasma treatments of porous and compact TiO2 substrates were explored as a function of plasma precursor, substrate location in the plasma, applied rf power, and plasma pulsing parameters. Continuous wave O2 plasma treatments were found to reduce carbon content and increase oxygen content in the films. Experiments also reveal that Si was deposited throughout the mesoporous network and by pulsing the plasma, Si content and film damage could be eliminated. Nitrogen doping of TiO2 films (N:TiO2) was accomplished by pulsed plasmas containing a range of nitrogen precursors. N:TiO2 films were anatase-phased with up to 34% nitrogen content. Four different nitrogen binding environments were controlled and characterized. The produced N:TiO2 films displayed various colors and three possible mechanisms to explain the color changes are presented. Both O2 treated and N:TiO2 materials were tested in photocatalytic devices. Preliminary results from photocatalytic activities of plasma treated P25 TiO2 powders showed that nitrogen doping treatments hinder photocatalytic activity under UV light irradiation, but silicon deposition can improve it. N:TiO2 materials were tested in photovoltaic devices to reveal improved short-circuit current densities for some plasma-modified films. To understand the gas-phase and surface chemistry involved in producing the N:TiO2 films, NH and NH2 species in pulsed NH3 plasmas were explored by systematically varying peak plasma power and pulsing duty cycle. Results from these studies using gas phase spectroscopy techniques reveal interconnected trends of gas-phase densities and surface reactions. Gas-phase data from pulsed plasmas with two different types of plasma pulsing reveal diminished or increased densities at short pulses that are explained by plasma pulse initiation and afterglow effects. Overall this work reveals characteristics of the plasma systems explored, knowledge of the resulting materials, and control over plasma etching, deposition, and modification of TiO2 surfaces.
Keywords: laser induced fluorescence (LIF); x-ray photoelectron spectroscopy (XPS); TiO2; photodevices; plasma treatments; imaging of radicals interacting with surfaces (IRIS)